Viable AC Two-probe Impedance Spectroscopy based on Spatially-limited Contact Probe for SOFC Cathode - Lee, J. -H.; Ji, H. -I.; Kim, H. -R.; Son, J. -W.; Hwang, J. -H. (SOLID OXIDE FUEL CELLS 12 (SOFC XII), 2011)
We repor on a unique characterization method for the electrode reactions of SOFCs via impedance spectroscopy combined with a spatially-constricted contact based on a robust electrolyte which is expected to give more reliable measurement set-up. Various electrode materials were chosen to validate our method and the corresponding impedance phenomena were analyzed to give an insight for optimization of the SOFC electrode. The ramifications of "limited-contact" impedance spectroscopy are discussed for an exhaustive understanding of electrode-related polarizations in SOFCs.